How Profitability, Thin Capitalization, and Company Size Affect Tax Avoidance - Ayatilla, Nadien; Permatasari, Intan Kurnia (PT Aksara Indo Rajawali, 2024)
The aim of this research is to obtain empirical evidence of the influence of profitability, thin capitalization, and company size on tax avoidance. This research is a quantitative research. Profitability variable is measured using the Return on Asset Ratio. Thin Capitalization variable is measured using the Debt to Equity Ratio. Company Size variable is measured using Natural Logarithm of Total Asset. Tax Avoidance variable is measured using Effective Tax Rate. 94 sample companies were obtained after purposive sampling, in the form of manufacturing sector companies listed on the IDX between year 2019 until 2021. The data was tested using multiple linear regression analysis techniques including classical assumption test, F Test, T Test, and coefficient of determination with the help of IBM Statistics SPSS 23 software. The results of this research profitability had a negative effect on tax avoidance, thin capitalization does not affect tax avoidance, and company size does not affect tax avoidance.